2021
DOI: 10.1017/pasa.2021.48
|View full text |Cite
|
Sign up to set email alerts
|

The radioactive nuclei and in the Cosmos and in the solar system

Abstract: The cosmic evolution of the chemical elements from the Big Bang to the present time is driven by nuclear fusion reactions inside stars and stellar explosions. A cycle of matter recurrently re-processes metal-enriched stellar ejecta into the next generation of stars. The study of cosmic nucleosynthesis and this matter cycle requires the understanding of the physics of nuclear reactions, of the conditions at which the nuclear reactions are activated inside the stars and stellar explosions, of the stellar ejectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 278 publications
(346 reference statements)
0
20
0
Order By: Relevance
“…Potential sources include AGB stars, novae, core-collapse supernovae, and Wolf-Rayet (W-R) star winds (Prantzos & Diehl 1996;Diehl et al 2006). A very recent review of the nucleosynthesis reactions involved in the production and destruction of 26 Al and 60 Fe and characteristics of the stellar sites of their nucleosynthesis can be found in Diehl et al (2021).…”
Section: Low-energy Excesses In Lithium Fluorine Aluminum and Ironmentioning
confidence: 99%
“…Potential sources include AGB stars, novae, core-collapse supernovae, and Wolf-Rayet (W-R) star winds (Prantzos & Diehl 1996;Diehl et al 2006). A very recent review of the nucleosynthesis reactions involved in the production and destruction of 26 Al and 60 Fe and characteristics of the stellar sites of their nucleosynthesis can be found in Diehl et al (2021).…”
Section: Low-energy Excesses In Lithium Fluorine Aluminum and Ironmentioning
confidence: 99%
“…We then assume 10 4 outbursts in total during the life of a nova system. a ratio in the range 0.2 − 0.4: as stated by Diehl et al (2021), this flux ratio can be converted into a mass ratio that lies in the range 0.7 − 1.5M . Therefore, by assuming that the best 26 Al mass observation is 2 M , 60 Fe mass should lie in the range 1.4 − 3.0 M .…”
Section: Fe Massmentioning
confidence: 96%
“…But they assumed relatively large energies for the supernova neutrinos that are not supported by current simulation results. The contribution of the neutrino process is significantly reduced to about 10% when the lower neutrino energies are adopted (Sieverding et al 2018;Diehl et al 2021). So the previous studies have suggested that about 0.2 M e of 26 Al is contributed by the neutrino process.…”
Section: Introductionmentioning
confidence: 97%
“…In the early 2000s, the present total mass of 26 Al in the Milky Way was determined to be 2.8 ± 0.8 M e from γ-ray observations (Diehl et al 2006). Now, the observations constrain it to fall between 1.7 and 3.5 M e , with a best estimate of 2 M e (Diehl et al 2021). Timmes et al (1995a) have estimated that the 26 Al yield can be increased by 40% with the neutrino process.…”
Section: Introductionmentioning
confidence: 99%